Thermal Degradation Study of Salicylic Acid, Diaminonaphthalene and Formaldehyde Terpolymer - Dhanraj T. Masram (E-Journal of Chemistry)
The terpolymer resin salicylic acid-diaminonaphthalene-formaldehyde (SDNF) has been synthesized by the condensation of salicylic acid and diaminonaphthalene with formaldehyde in the presence of catalyst hydrochloric acid in 1:1:2 molar proportions of reactants. Detailed thermal degradation studies of the SDNF terpolymer resin has been carried out to ascertain its thermal stability. Thermal degradation curve has been discussed in order to determine their mode of decomposition, order of reaction, apparent activation energy, frequency factor, free energy change, entropy change, and apparent energy change. Freeman – Carroll and Sharp- Wentworth methods have been applied for the calculation of kinetic parameters while the data from the Freeman – Carroll methods have been used to determine various thermodynamic parameters.